ANALISIS KUALITAS PELAYANAN PADA STUDIO BARBERSHOP - Lukas Leko Pati; Ni Luh Putu Erma Mertaningrum; Cokorda Istri Mas Kusumaningrat (Jurnal Ilmu Sosial dan Ilmu Politik, 2023)
This study aims to measure the quality of service provided by Studio Barbershop. This research was conducted because there were customer complaints about this barbershop’s service. The number of respondents involved in this study was sixty. The numbers of the respondents who were under 20 years old, 20-30 years old, 31-40 years old, and 41-50 years old were respectively 10 (16.7%), 33 (55%), 9 (15%), and 8 (13.3%). The service quality of Studio Barbershop, based on all parameters, reached a score of 3,194. This figure was in the score range of 3,025 to 3,600. Thus, the quality of service provided by Studio Barbershop was classified as very good. The quality of service in terms of tangibility only reached a total score of 197 which was in the score range of 157 to 204. Therefore, it was classified as quite good.